Analyzing the Impacts of Plastic Wastes in Water Bodies and Suitable Methodology to Prevent It - Yasin, Razia; Tehseen, Palwasha; Shakir, Tayyba; Mumtaz, Ayesha; Subtain, Muhammad; Abbas, Aqsa; Naeem, Mashal; Zaman, Mariam; Manzoor, Mehwish (Indonesian Journal of Agriculture and Environmental Analytics, 2024)
Plastics are widely distributed across organisms of various trophic levels and in terrestrial, freshwater, marine, and other environments. Recently, plastics have emerged as significant environmental pollutants, attracting public concern. This systematic literature review identifies sources of plastic waste, including food packaging, household hazardous waste, and wood waste, highlighting their detrimental impacts on water bodies, environmental health, and animal life. Analytical techniques such as Scanning Electron Microscopy (SEM), Atomic Absorption Spectroscopy (AAS), and Differential Scanning Calorimetry (DSC) are essential for detecting and quantifying plastic pollutants. Prevention strategies, including source reduction, public awareness campaigns, legislative measures, and the implementation of pollution control techniques, are crucial in mitigating plastic waste in water bodies. Future research should focus on developing innovative materials and sustainable alternatives to plastics, enhancing waste management infrastructure, and fostering global collaboration to address the plastic pollution crisis effectively.